Effect of crystallographic orientation on tensile fractures of (100) and (110) silicon microstructures fabricated from silicon‐on‐insulator wafers. (1st December 2015) - Uesugi, Akio; Hirai, Yoshikazu; Sugano, Koji; Tsuchiya, Toshiyuki; Tabata, Osamu
Abstract : This Letter investigates the effect of crystallographic orientation on tensile fractures of silicon microstructures. Specimens 5 μm wide and 5 μm thick were fabricated on (100) and (110) wafers with 〈100〉, 〈110〉, and 〈111〉 tensile axes. To explore the effects of different surface orientations and morphologies, these specimens were patterned from (100) and (110) silicon‐on‐insulator (SOI) wafers using the Bosch process under identical fabrication conditions, while other specimens were fabricated from (110) wafers under different conditions. Tensile tests of specimens prepared under the identical fabrication conditions showed that (100) specimens had lower strength than (110) specimens along the 〈100〉 and 〈110〉 axes; the average strength decreased from 3.62 to 3.14 GPa for 〈110〉. This decrease in strength is related to differences in damage that ultimately causes fractures. While (110) specimens fractured due to fabrication damage at top corners, fractures of (100) specimens were due to pit‐like defects on bottom surfaces. Since these defects were introduced during SOI bonding processes, the fractures of (100) specimens were dominated by intrinsic SOI defects rather than damage introduced during specimen fabrication processes. To realise higher‐strength structures on SOI wafers, both the damage caused during fabrication and the intrinsic defects need to be controlled.